Spatiotemporal analysis of sea surface temperature and chlorophyll-a variability under ENSO-IOD influence in the Southern Madura Strait, Indonesia - Yarkhasy Yuliardi, Amir; Napitupulu, Gandhi; Aulia Rachman, Herlambang; Prayogi, Harmon; Ika Joesidawati, Marita; Djanat Prasita, Viv (Vietnam Journal of Earth Sciences, 2025)
A dynamic interplay between local oceanographic processes and large-scale climate drivers shapes tropical coastal ecosystems. Yet, their coupled responses remain poorly quantified in many regions of the Indonesian Maritime Continent. This study examines the spatiotemporal variability of sea surface temperature (SST) and chlorophyll-a concentrations in the southern Madura Strait, utilizing 15 years (2010–2024) of monthly MODIS-Aqua observations, in conjunction with Niño 3.4 and Dipole Mode Index (DMI) time series to characterize ENSO and IOD phases. Monthly climatologies revealed a pronounced SST annual cycle, with peak warming during December-February (DJF) and March-May (MAM) (±31°C) and basin-wide cooling during June-August (JJA, ±28°C). Chlorophyll-a exhibited strong spatial heterogeneity, with the highest biomass (>10 mg/m³) consistently observed in the western sector during DJF and MAM, likely reflecting monsoon-driven circulation and terrestrial nutrient inputs. Composite analyses revealed that La Niña and negative IOD phases increased productivity through surface cooling and nutrient enrichment. In contrast, El Niño and positive IOD phases resulted in compound warming events that suppressed chlorophyll-a. Lagged correlation analyses further revealed that chlorophyll-a responses typically lag climate anomalies by one to two months, underscoring the temporally asynchronous nature of climate-ecosystem interactions. These results provide new process-based insights into how ENSO-IOD interactions regulate tropical coastal productivity, highlighting the importance of incorporating climate drivers and temporal lags into forecasting and adaptive fisheries management frameworks to maintain ecosystem resilience under future climate variability.